Selection of upland rice cultivars for saline-sodic soils. II. field trials - Gheyi, Hans Raj; Barreto, Aurelir Nobre; Garri, Arturo Carlos R. Carvajal; Almeida, Aresque Machado de (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment in a saline-sodic soil of the irrigated perimeter of São Gonçalo-Sousa, PB, Brazil, was carried out with the objective to select cultivars of irrigated rice (Oryza sativa L.) for salt affected soils. A random block design with thirteen cultivars and three replications was adopted. Before the start of the experiment, 40 t/ha of gypsum were incorporated in the soil, and N, P2O5 and K2O were applied at the rate of 5O, 30 and 10 kg/ha, respectively. The cultivars under study showed significant yield differences at 0.01 probability level and a mean production of 6.12 t/ha was obtained for the cultivar IR 2058-78-1-3-2-3. Considering the high exchangeable sodium percentage and the fact that experimental plot has not been cultivated for many years, the results obtained show the viability of utilization and reclamation of such soils with gypsum and rice cultivars.